Design and Fabrication of 3D Printed Remotely Operated Vehicles (ROVs) for Shallow Underwater Environmental Monitoring - Che Alias, Muhammad Zulfauzan Fahmi; Abdul Kadir, Herdawatie; Mod Arsad, Nur Nazifa; Isa, Khalid; Mohammad Razi, Mohd Adib; Ambar, Radzi; Mohd Ibrahim, Iffan Darwis (International Journal of Integrated Engineering, 2026)
The vitality of aquatic ecosystems is essential for biodiversity, water quality, and comprehensive environmental sustainability. However, exploring underwater environment poses many challenges due limited accessibility, and the high expense of monitoring equipment. Nowadays, ROVs has emerged as a viable solution that provides a cost-efficient and customizable method, facilitating the swift creation and deployment of lightweight, high-performance vehicles designed for specific monitoring purposes. Nevertheless, designing ROVS involves optimizing hydrodynamic efficiency through streamlined shapes and propeller designs. The design, material selection, and thruster system of ROVs are crucial for their performance, durability, and operational effectiveness in underwater environments. This work integrates the ROV control module with custom 3D printing design which is name as ‘3DSeaProbe’. The ABS Glass Fiber filament is used in 3D printing which enhances the material’s properties, making it more rigid and robust. Six-thruster configuration is employed for the ROV manoeuvrability capability. The 3DSeaProbe can reach depth and manoeuvre up to 50 meters and is able to be used in a range of underwater applications, surveillance, operations, maintenance, and measurement.